CHALLENGES OF ENGLISH TEACHERS IN THE DIGITAL ERA - Fauzi , Iwan (UICELL, 2023)
Today's connected knowledge provides teachers and students with fast and easy access to the latest information and communication technology (ICT). The time has come to equip communities around the world with digital literacy skills. English teachers are no exception to the ability to access, analyze, and engage with digital technology and its varieties to support their students in learning. In the digital era where an English teacher is one of the users who also utilize its sophisticated tools, they need not only acquire digitalized pedagogical skills but also the ability to use these skills smartly. One way this can be achieved is by improving teachers’ ICT skills as well as their attitude toward the ICT itself. The objective of this paper is to review and elaborate on how English teachers integrate digital technology to create innovative instructional learning models to face the age of digital learning, then how well-prepared they are. In addition, this paper also provides a recommendation to the authorities concerning the facility and digitized school infrastructures to have ICT more integrated into education settings.